The role of e-commerce in stimulating innovative business development in the conditions of European integration - Вербівська, Людмила Василівна (Financial and credit activity-problems of theory and practice, 2023)
Electronic commerce is of great importance for consumers, business founders and the state. Users get the opportunity to order goods and services anywhere and anytime, business founders have access to the global market and expanded sales opportunities. In addition, e-commerce has a significant impact on the growth of the economy due to its ever-increasing share in the GDP of countries. The purpose of this study is to determine the level of development of e-commerce in Ukraine compared to other countries of the world and to study its impact on the innovative development of businesses in modern conditions. The research used the following methods: economic-statistical analysis, comparative analysis, the method of establishing cause-and-effect relationships. As a result of the study, the state of indicators of the development of e-commerce in Ukraine at the current stage was characterized. The share of Internet users from the total population in Ukraine was determined, and the percentage of those who make purchases via the Internet was determined. The share of e-commerce in Ukraine's GDP is characterized, as well as its dynamics over the last period. It was determined which industries and web resources are the most popular in Ukraine and compared this data with the global data. Global trends in the development of e-commerce in comparison with Ukrainian trends are outlined. The ranking of countries according to key indicators related to the development of e-commerce, the number of online buyers in the countries, the share of e-commerce in the GDP of countries, etc. is given. The obtained results can be used by business founders for a general understanding of trends in the field of e-commerce and when choosing a business direction.
Verbivska, L., Zhuk, O., Ievsieieva, O., Kuchmiiova, T., & Saienko, V. (2023). The role of e-commerce in stimulating innovative business development in the conditions of European integration. Financial and credit activity-problems of theory and practice, 3(50), 330-340
Keywords: E-commerce, innovation, business, internet, online buyers, target audience